(E)-1-(Anthracen-9-yl)-3-(2-chloro-6-fluorophenyl)- prop-2-en-1-one: crystal structure and Hirshfeld surface analysis - Abdullah, Amzar Ahlami; Hassan, Nur Hafiq Hanif; Arshad, Suhana; Che Khalib, Nuridayanti; Razak, Ibrahim Abdul (International Union of Crystallography, 2016)
In the title compound, C23H14ClFO, the enone moiety adopts an E conformation. The dihedral angle between the benzene and anthracene ring is 63.42 (8)° and an intramolecular C—H⋯F hydrogen bond generates an S(6) ring motif. In the crystal, molecules are arranged into centrosymmetric dimers via pairs of C—H⋯F hydrogen bonds. The crystal structure also features C—H⋯π and π–π interactions. Hirshfeld surface analysis was used to confirm the existence of intermolecular interactions.